Effective Web Development Through Quality of Information Thereby Increasing its Agility - Abdul-Aziz, Azlianor; Sulong, Muhammad Suhaizan; Koronios, Andy; Gao, Jing (Publications International, 2013)
The emergence of the Internet has had a huge impact on individuals and businesses as is the case with many great web-based information systems that we see today offer convenience, efficiency, better service and savings. Developing one can be a challenging undertaking considering the nature of the web, its unique characteristics, requirements and factors. Hence, without suitable methodology, the entire webbased development would fail. With this reason, this paper presents the application of information quality techniques into the web-based development process to improve agility. This approach will accrue significant benefits and cost savings for web development teams and organisations to effectively design and develop web-based information systems.